Government programs to support motherhood and childhood in the USA - Viktoriia Stynska (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the issue of government programs to support motherhood and childhood in the USA: Aid to families with dependent children Program; Work Initiative Program; Job Opportunity and Basic Skills Training Program; Food stamps Program; Emergency Assistance Program, Family Access to Medical Insurance Security Program; Social Security Program and others. The legislative frame work that helped to implement state programs to support social policy in the USA, namely Family Support Act, Social Security Act, Child Support Enforcement Act and others, was analyzed. Key words: social benefit, government program, motherhood, childhood, the USA.